The influence of running performance on scoring the first goal in a soccer match - Klemp, M.; Memmert, D.; Rein, R. (spinfortec2020digital: 13. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 24.-25. September 2020 in Bayreuth, 2020)
This study aimed at examining the influence of a team`s running performance on its probability of scoring the first goal in a soccer match. A predictive study design was used, controlling for contextual variables, especially score line. Amongst those metrics which are commonly reported post-game, running distance has a prominent role in soccer. However, while running distance is mostly used to assess external load and efforts, its relation to game success is unclear at present. The present study revealed a positive relationship between running performance and success. The ways in which running affects the probabilities of goal scoring have yet to be elucidated. Further research should clarify the responsible mechanisms for this correlation.